Determinants of Access to Trainings on Post -Harvest Loss Management among Maize farmers in Uganda: A Binary Logistic regression approach - Midamba, Dick Chune; Kizito, Ogei (Cogent Economics & Finance, 2022)
Post-harvest losses (PHL) reported in maize production put Sub-Saharan African countries at higher risks of food insecurity. Recent studies reported that higher percentage of PHLs occur during the production stage when farmers are in full control of the crop, suggesting that farmers are not equipped with PHL management skills. This study therefore aimed at assessing the determinants of access to trainings on PHL management among maize farmers in Uganda. Primary data were drawn from 246 randomly sampled farmers in Alebtong District followed by Binary logit analysis. The results depicted that majority of the farmers (58%) did not have access to PHL management trainings. However, those who had access sourced it from extension workers (40.65%), farmers’ groups (22.76%) and farmer-to-farmer trainings (12.20%). The main barriers limiting access to the trainings were unawareness of the PHL trainings and inaccessibility of the training centers. Farm size, group membership, maize output and marital status had positive effect on farmers’ access to PHL management trainings while farm location, and distance to the training centers had a negative effect on access to PHL management trainings. Based on the findings, there is need for public sensitization on the benefits of the PHL trainings, farmers should also be motivated to join farmer-based groups and association where they would learn more about the PHL trainings. In addition, the government should open more training centers and employ more training agents so that many farmers can be reached and trained on how to handle and mitigate PHLs in maize.
Keywords: Binary logit; Post – harvest losses; Training; Maize